Correlation of Red Cell Distribution Width with Stroke Severity and Short Term Functional Outcome in Acute Ischemic Stroke - Rahman, Aminur; Russel, Abul Hasnat Md; Yasmin, Sabina; Huq, Mohammed Nazmul; Khetan, Ajoy; Kabir, Shah Efrinul; Islam, Syed Sadib; Bhuiyan, Mohammad Shahidul Islam; Haque, SM Nazmul; Tasnim, Zarin; et al. (Bangladesh Journal of Medicine, 2025)
Background: Red cell distribution width (RDW) has been proposed as an independent predictor of acute ischemic stroke (AIS) severity and outcomes. This study aimed to evaluate whether RDW alone can serve as a predictor of functional outcome at three months following AIS. Methods: In this prospective cohort study (July 2024–June 2025), patients with AIS were categorized into quartiles based on admission RDW values. Baseline characteristics were compared using Pearson’s chi-square or Fisher’s exact tests for categorical variables and the Mann–Whitney U test for continuous variables. Univariable and multivariable binary logistic regression analyses were performed to identify predictors of three-month functional outcome, assessed by the modified Rankin Scale (mRS 0–2 vs. 3–6). Results: Most patients had RDW values between 12% and 15%, with a small subset showing elevated RDW (>16%). At three months, the majority achieved good recovery (mRS 0–2). In univariable analysis, lower diastolic blood pressure was associated with greater odds of functional independence, whereas smoking, higher NIHSS score at admission, and severe baseline disability were significantly associated with lower odds. In the multivariable model, smoking and severe disability at admission remained significant, while the NIHSS score was significant at the 10% level of significance. Conclusion: In this prospective cohort study, admission RDW was not independently related with three-month functional outcomes following acute ischemic stroke. The findings suggest that RDW has limited value as a standalone prognostic biomarker in the early post-stroke period. Bangladesh J Medicine 2025; 36(3): 91-100